Flotation using sodium dodecyl sulphate and sodium lauroyl isethionate for rapid dewatering of Mg(OH)2 radwaste suspensions. Issue 30 (24th May 2021) - Lockwood, Alexander P. G.; Shun, Philip Kok; Peakall, Jeffrey; Warren, Nicholas J.; Barber, Thomas; Basharat, Nabil; Randall, Geoff; Barnes, Martyn; Harbottle, David; Hunter, Timothy N.
Abstract : Mg(OH)2 suspensions were floated utilising sodium dodecyl sulphate (SDS) sodium lauroyl isethionate (SLI) collectors, for rapid dewatering of radwaste suspensions. Abstract : Mg(OH)2 suspensions were floated utilising sodium dodecyl sulphate (SDS) and sodium lauroyl isethionate (SLI) collectors, for rapid dewatering of radwaste suspensions. Freundlich adsorption isotherms were first used to compare the adsorption densities of SDS and SLI on Mg(OH)2 surfaces, to determine the maximum monolayer coverage capacity, and were found to be 0.11 μmol m −2 at a dosed concentration of 172 μM for SDS and 0.05 μmol m −2 at a dosed concentration of 188 μM for SLI. The natural and salt induced coagulation kinetics of Mg(OH)2 were examined using static light scattering, where the influence of collector adsorption on particle size distributions was also investigated, to probe potential hydrodynamic limitations of flotation. Particle stabilised foam formation was then characterised using a Bikerman column test, where the dynamic foamability indices (DFIs) of SDS and SLI were determined to be 49 × 10 3 s L mol −1 and 321 × 10 3 s L mol −1 respectively. Flotation performance was measured, and a collection efficiency factor used to compare the solid–liquid separation ability of mixed 2.5 vol% suspensions with SDS or SLI, as well as MIBC frother. Optimal performance aligned with collector concentrations relating to predicted maximum monolayer coverage, and whilst both surfactants were effective, SDS systems performed better than SLI in all metrics. Recoveries of >80% of the Mg(OH)2 wastes were achieved, whilst only transferring 35% of the water mass at the optimum SDS dosed concentration of 82 μM, likely due to its denser surface adsorption and minimised lamella water entrainment.